Radiosynovectomy in routine care: an old tool with modern applications. (November 2021) - Caballero Motta, Liz R.; Anzola Alfaro, Ana M.; Janta, Iustina; Molina Collada, Juan; Henao, Yulieth Katherine; Pérez Pascual, Rebeca; Álvaro-Gracia, José María; Nieto-González, Juan Carlos
Objectives: Radiosynovectomy can be an effective treatment for difficult-to-treat monoarthritis resistant to systemic and local standard therapy. The objective of our study was to determine predictors of good response to radiosynovectomy in routine care and give an overview of this underused technique. Methods: Retrospective observational study of all the patients who underwent radiosynovectomy during a 6-year inclusion period. All the procedures were ultrasound guided and the radiopharmaceutical used was chosen according to joint size. The patient was considered to have an effective response to radiosynovectomy if the attending physician reported a positive outcome and there was no need to increase local and or systemic treatment due to arthritis in the affected joint during the next 12 months following the procedure. Results: We included 67 patients who underwent radiosynovectomy in the knee (73.1%), wrist (16.4%), and elbow (10.5%). Overall, 44 (65.7%) procedures were considered effective. In the multivariate analysis, infiltration of wrists (odds ratio = 0.192; confidence interval = 0.046–0.79) and pigmented villonodular synovitis (odds ratio = 0.13; confidence interval = 0.021–0.82) were independently associated with a noneffective response. No patients experienced complications associated with radiosynovectomy during follow-up. Conclusion: Infiltrations of wrists with joint damage seem less likely to have a response to radiosynovectomy. In pigmented villonodular synovitis, radiosynovectomy as an adjuvant therapy for relapse might not be effective when performed more than 6 months after surgery. Overall, radiosynovectomy is an effective and safe treatment for persistent monoarthritis.